Increased numbers of CD23+CD21hi Bin‐like B cells in human reactive and rheumatoid arthritis lymph nodes. Issue 7 (6th May 2016) - Kuzin, Igor I.; Kates, Stephen L.; Ju, Yawen; Zhang, Longze; Rahimi, Homaira; Wojciechowski, Wojciech; Bernstein, Steven H.; Burack, Richard; Schwarz, Edward M.; Bottaro, Andrea
Abstract : During inflammatory responses, lymph nodes undergo extensive changes in architecture and cellular composition. A population of B cells (B cells in inflamed nodes, or Bin cells), with characteristic surface phenotype and functional features, accumulates in mouse inflamed lymph nodes, especially in arthritis models. In this manuscript we report that phenotypically similar B cells are also found in high numbers in human reactive and rheumatoid arthritis lymph nodes. Abstract : A unique population of CD23 + CD21 high B cells ini nflamedn odes (Bin) has been shown to accumulate in lymph nodes (LNs) draining inflamed joints of TNF‐transgenic (TNF‐tg) mice. Bin cells contribute to arthritis flare in mice by distorting node architecture and hampering lymphatic flow, but their existence in human inflamed LNs has not yet been described. Here, we report the characterization of resident B‐cell populations in fresh popliteal lymph nodes (PLNs) from patients with severe lower limb diseases (non‐RA) and rheumatoid arthritis (RA) patients, and from banked, cryopreserved reactive and normal human LN single cell suspension samples. Bin‐like B cells were shown to be significantly increased in reactive LNs, and strikingly elevated (>30% of total) in RA samples. Histopathology and immunofluorescence analyses were consistent with B follicular hyperplasia and histological alterations in RA vs. non‐RA PLNs. This is the first description of Bin‐like B cells in human inflamed LNs. Consistent with published mouse data, this population appears to be associated with inflammatory arthritis and distortion of LN architecture. Further analyses are necessary to assess the role of CD23 + CD21 hi Bin‐like B cells in RA pathogenesis and arthritic flare.